2017
DOI: 10.5812/hepatmon.58739
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Seroprevalence and Associated Risk Factors Among Male Drug Injectors in Kermanshah, Iran

Abstract: Background: Infection with hepatitis C virus (HCV) is increasingly recognized as a major global health problem. Objectives: The aim of this study was to measure the prevalence of HCV infection and determine the risk factors associated with HCV among male people who inject drugs (PWID) in Kermanshah, Iran. Methods: In this cross sectional study, the samples were recruited from 2 drop-in centers and related community outreach sites, using snowball sampling. The questionnaire consisted of 3 sections, including de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…Regarding sociodemographic factors, age, and education level was significant risk factors for HCV infection that is similar to the results of Iranian study[ 17 ] that reported association between age and HCV infection. Education provides information about the diseases, mode of transmission and how to prevent it.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding sociodemographic factors, age, and education level was significant risk factors for HCV infection that is similar to the results of Iranian study[ 17 ] that reported association between age and HCV infection. Education provides information about the diseases, mode of transmission and how to prevent it.…”
Section: Discussionsupporting
confidence: 88%
“…Reducing disease prevalence in any country requires not only enhanced rates of diagnosis and treatment but also strategies to prevent new infections. Regarding sociodemographic factors, age, residence, education level, and marital status were significant risk factors for HCV infection that is similar to the results of different studies [14][15][16]. On the other hand, a study [17] in Egypt showed no association between age and HCV infection.…”
Section: Discussionsupporting
confidence: 85%
“…Needle pricking ratio was very high in local setup. Previous studies conducted in Iran analyzed strong association of HCV seropositive with injections, tattooing, sharing equipment and history of imprison (Mir-Nasseri et al, 2011;Nokhodian et al, 2012;Sharhani et al, 2017). Previous studies on needle pricking, recapping needle pricking syringes were responsible for 2 to 10% transmission of hepatitis C in health care worker (Hamid et al, 1999;Mujeeb et al, 1998;Aziz et al, 2002) another study in Mirpur Khas, Hyderabad and Sukkur the incident of hepatitis C virus among the population sharing reused of injection equipment were reported 68%, 8.5% and 33.6% respectively (Altaf et al, 2009;Janjua et al, 2005).…”
Section: Discussionmentioning
confidence: 99%